A Note on the Occurrence of Anthracnose Disease on Mango in Kordofan, Sudan (University of Khartoum Journal of Agricultural Sciences, 2025)
Mango anthracnose was first seen on 9 June 2007 in localized spots in aseeded mango (cv. ‘Baladi’) orchard in Abu Gebiaha, South Kordofan State. The diseasewas also recorded in five surveyed areas in south and north Kordofan. The leafsymptoms included small, angular, brown to black spots, which may enlarge to formextensive dead areas. Colletotrichum gloeosporioides Penz and Sacc. was isolated fromthese spots and its pathogenicity was verified on non-symptomatic trees (cv. Baladi). Asfar as we know, this is the first report of mango anthracnose disease in Kordofan, Sudan.The symptoms were also observed on the mango cultivars ‘Abu Samaka’ and ‘Temour’.Due to the susceptibility of the mango cultivars that are currently planted in these areas,mango anthracnose is expected to cause a serious loss in mango production in Kordofanif favorable climatic conditions for the disease development prevail
Keywords: Mango; anthracnose disease; Sudan